Stories from precariousness: Territorial relocations, dispossession and resistance in Santiago del Estero, Argentina - Hernández, Juliana; Saccucci, Erika (Universidad del Pacífico, 2020)
This paper addresses the issue of precarity based on the territorial relocation of populations in the city of Santiago del Estero, Argentina. Working with a flexible methodology based on  multiple-case and discourse analysis, we analyze sixteen in-depth interviews with institutional agents and residents of the city. Precarity emerges as the articulating category of the stories through the configuration of dispositives of power and the interposition of resistance and struggles. We conclude that relocation creates new precarities that should be understood in terms not only of the loss of living conditions, but also of their de-subjectifying effects.